2015
DOI: 10.1038/srep09032
|View full text |Cite
|
Sign up to set email alerts
|

The transmembrane transporter domain of glutamate transporters is a process tip localizer

Abstract: Glutamate transporters in the central nervous system remove glutamate released from neurons to terminate the signal. These transporters localize to astrocyte process tips approaching neuronal synapses. The mechanisms underlying the localization of glutamate transporters to these processes, however, are not known. In this study, we demonstrate that the trimeric transmembrane transporter domain fragment of glutamate transporters, lacking both N- and C-terminal cytoplasmic regions, localized to filopodia tips. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…The TM transporter domains of the two glutamate transporters (mEGFP‐GLT1‐TM and mEGFP‐GLAST‐TM), with all TM helices and their connecting loops, but without cytoplasmic tails, localized to cellular process tips. This result shows that cellular process tip localization is a common feature of trimeric TM transporters, while the cytoplasmic tails of GLT1 facilitate plasma membrane delivery (Hayashi and Yasui ).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The TM transporter domains of the two glutamate transporters (mEGFP‐GLT1‐TM and mEGFP‐GLAST‐TM), with all TM helices and their connecting loops, but without cytoplasmic tails, localized to cellular process tips. This result shows that cellular process tip localization is a common feature of trimeric TM transporters, while the cytoplasmic tails of GLT1 facilitate plasma membrane delivery (Hayashi and Yasui ).…”
Section: Resultsmentioning
confidence: 86%
“…The difference in action of hyaluronidase from bovine testis and Streptomyces hyalurolyticus we observed could be attributed to whether these hyaluronidases are able to trim short hyaluronan chains anchored to HAS so that newly synthesized hyaluronan do not reach glutamate transporters. We previously reported that an extracellular loop connecting the transport subdomain and trimerization subdomain of GLT1 is required for cellular process localization (Hayashi and Yasui ). We speculate that the interaction between the extracellular loop of GLT1 and a short chain of hyaluronan anchored to neighboring hyaluronan synthase affects conformational change between subdomains for substrate transport.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal glutamate release determines retraction of APs, reducing then astrocyte capability to effectively remove glutamate from synapses, even if a recent study shows that glutamate transporters influence APs tip position [66]. In these conditions, ATP derived from astrocytes might lose its capability to act on neighboring neurons [67] impairing synaptic transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The glutamate transporters glutamate transporter 1 (GLT1) and glutamate aspartate transporter (GLAST) are highly expressed on astrocytes [121,122]. We have shown that ghrelin treatment icv rapidly stimulates GLT1 and GLAST levels, while only GLAST levels were found to increase in vitro [19].…”
Section: Ghrelin and Astrocytes In Metabolic Controlmentioning
confidence: 99%